Distinct binding strategies of plasma proteins on gold surfaces: flexibility versus stability in the protein corona formation - Cipriani, Beatrice; Lopez, Hender; Brancolini, Giorgia (Frontiers in Nanotechnology, 2025)
When in contact with biological matrices, gold nanoparticles (AuNPs) become coated with a protein corona, which governs their biological identity and mediates interactions with cells and tissues. This study explores the adsorption behavior and conformational dynamics of two key plasma proteins, human serum albumin (HSA) and transferrin (TRF), on AuNP surfaces using Brownian Dynamics (BD) and atomistic Molecular Dynamics (MD) simulations. The results reveal multiple binding mechanisms for HSA and TRF on Au (111) surfaces. HSA exhibits significant reorientations during binding, initiated by negatively charged residues and stabilized by hydrophilic amino acids, with its structural rigidity requiring multiple reversible anchoring attempts before achieving more energetically favorable interactions. In contrast, TRF demonstrates rapid and stable binding due to its intrinsic local flexibility, retaining docked orientations with minimal reorientation. While both proteins utilize electrostatic interactions to approach the surface, TRF’s disordered structure enables swift adaptation, whereas HSA’s rigidity supports strong interactions upon relaxation. These findings highlight contrasting binding strategies, with TRF prioritizing speed and flexibility, and HSA exploiting domain rearrangements for sustained stability. Importantly, the results obtained at the all-atom level of resolution are critical for the development of coarse-grained and mesoscale models. The approach in classifying protein orientation enhances our understanding of the protein corona’s shape and morphology and could advance its effective representation in lower-resolution models. The insights gained from these simulations enable us to analyze the different adsorption behavior of TRF and HSA, providing a deeper understanding of how their structural properties influence protein corona formation.